(3GdCZPjI hGdCTQHI heG jJUd HgGs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s ((3eMeO Hf eMeO Hf eSYhO s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GdYGdejf aCbhd Cf GdZPGA GdMbjbi gh GdPi jbhe ebGe LhGgQ GYVGA GdHOf hjUjQ HOdkG dg s
(3BNQgG (B:s
(3adGjNai Jbhi GdfaS hGdQhM hGdHOf hGfJYGTgG HQhGFM GdGWYeI hCTO ef GSJYeGd SGFQ GdQhGFM GdWjHI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
Keywords: (3GdWHs